2009
DOI: 10.1007/s11336-009-9117-0
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Model Comparison for the Order Restricted RC Association Model

Abstract: contingency tables, ordinal variables, reversible jump MCMC algorithm, equality of odds, Bayesian model averaging,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Additionally, the last level of the disturbance is homogeneous with respect to the second and third levels in the RC5 model. These inferences are in accordance with those given by Iliopoulos et al [20,21] and maximum likelihood estimates (MLEs) given by the other authors mentioned. However, we identify the unrestricted RC model as the best one among all of the models, whereas Iliopoulos et al [20] identified the RC4 model as the best based on a criterion-based comparison.…”
Section: An Illustrative Examplesupporting
confidence: 92%
See 4 more Smart Citations
“…Additionally, the last level of the disturbance is homogeneous with respect to the second and third levels in the RC5 model. These inferences are in accordance with those given by Iliopoulos et al [20,21] and maximum likelihood estimates (MLEs) given by the other authors mentioned. However, we identify the unrestricted RC model as the best one among all of the models, whereas Iliopoulos et al [20] identified the RC4 model as the best based on a criterion-based comparison.…”
Section: An Illustrative Examplesupporting
confidence: 92%
“…Therefore, we assume the independence of scores while imposing order restrictions on scores, following the work of Iliopoulos et al [20,21]. We use order statistics to represent order restrictions.…”
Section: Prior Distributions For Unrestricted and Order-restricted Casesmentioning
confidence: 99%
See 3 more Smart Citations